Effects of arsenic and moisture regime on nutrient content and their uptake by NERICA rice - Bhattacherjee, S; Chowdhury, MAH; Rahman, MH; Saha, BK (Journal of the Bangladesh Agricultural University, 2016)
A pot experiment was carried out in the net house of Bangladesh Institute of Nuclear Agriculture (BINA) to study nutrient content and their uptake by different rice varieties (NERICA-1, NERICA-10 and BRRI dhan48) in response to different levels of arsenic (As) under varying moisture regimes. Three levels of As were added viz. 0, 30, 60 ppm to the pot soil from sodium arsenate (Na2HAsO4. 7H2O). After establishment of crops the moisture level of soil was adjusted to maintain flooded, 50% and 100% field capacity condition during crop growing period. The experiment was laid out in a Completely Randomized Design (CRD), with three replications. The amount of N, P, K, S and Zn was calculated as per their rate of application and was applied to the individual pot. Higher levels of As adversely affected the nutrient content and their uptake by rice except N contents. Nitrogen content increased with the increase of As level. Higher amount of nutrient content and uptake was recorded in BRRI dhan48 and flood condition enhanced higher nutrient content as well as uptake by rice. This study suggests the possible management of moisture regime and considering less As susceptible variety, which might reduce the toxic effects of As on nutrient uptake. J. Bangladesh Agril. Univ. 12(2): 291-296, December 2014